2017
DOI: 10.7150/thno.18078
|View full text |Cite
|
Sign up to set email alerts
|

Improved Tumor Uptake by Optimizing Liposome Based RES Blockade Strategy

Abstract: Minimizing the sequestration of nanomaterials (NMs) by the reticuloendothelial system (RES) can enhance the circulation time of NMs, and thus increase their tumor-specific accumulation. Liposomes are generally regarded as safe (GRAS) agents that can block the RES reversibly and temporarily. With the help of positron emission tomography (PET), we monitored the in vivo tissue distribution of 64Cu-labeled 40 × 10 nm gold nanorods (Au NRs) after pretreatment with liposomes. We systematically studied the effectiven… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
65
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 117 publications
(66 citation statements)
references
References 38 publications
1
65
0
Order By: Relevance
“…Liposomes are sterically stabilized by attaching polyethyleneglycol (PEG) at the outer membrane and shielded from opsonization, liver uptake, 6,7 and sequestration by the reticuloendothelial system (RES). 8 By escaping the RES, liposomes circulate longer in blood, and eventually tumor-specific accumulation of liposomes is increased. 9 These PEGylated liposomes can be further functionalized by decorating the surface with antibodies 7,10 specific to tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…Liposomes are sterically stabilized by attaching polyethyleneglycol (PEG) at the outer membrane and shielded from opsonization, liver uptake, 6,7 and sequestration by the reticuloendothelial system (RES). 8 By escaping the RES, liposomes circulate longer in blood, and eventually tumor-specific accumulation of liposomes is increased. 9 These PEGylated liposomes can be further functionalized by decorating the surface with antibodies 7,10 specific to tumor cells.…”
Section: Introductionmentioning
confidence: 99%
“…The second aim of the study was the application of a molecular imaging system to follow up the biodistribution of the PEG-liposome-encapsulated antitumor drugs. The human reticuloendothelial system and immune cells have been found capable of capturing the circulated liposomes (46) and, at the same time, the biodistribution of these liposome-encapsulated drugs among the organs are very important in clinical practice but not easy to follow-up. In 2007, Papahadjopoulos et al, found that the cumulative amounts of conventional liposomes in the liver and the spleen can reach a significant level at 2 h after intravenous injection, while the amounts of PEG-liposomes were relatively low.…”
Section: Discussionmentioning
confidence: 99%
“…The zeta-potential of the prepared SLNs ranged from −20.86 to −16.47 mV. It was reported that a slightly negatively nanoparticle could decrease reticuloendothelial system (RES)-mediated clearance, and eventually increase circulation time [41]. MTO and βE were efficiently loaded within SLNs, and the EE% of all the prepared SLNs was higher than 90%.…”
Section: Characterization Of Slnsmentioning
confidence: 99%